2020
DOI: 10.1111/1759-3441.12279
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Monetary Policy Shocks on Income Inequality Across U.S. States

Abstract: Using a time series cross‐state panel data of 50 U.S. states and the District of Columbia (DC) over the period of 1959 through 2015, this article intends to assess the direct and indirect effects of contractionary monetary policy shocks on income inequality through interest rate and consumer price index (CPI) inflation channels. To address this, the authors examine two possible linear and non‐linear relationships between inflation and income inequality and between gross domestic product (GDP) and income inequa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 56 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…The total influence of monetary policy (MP) on income inequality is theoretically unclear (Mäki-Fränti et al , 2022). However, some researchers indicate that expansionary and contractionary monetary policy reduces/increases income inequality (Andersen et al , 2021; Taghizadeh‐Hesary et al , 2020; Siami‐Namini et al , 2020; Hohberger et al , 2019). In their study, Adediran et al (2017) showed that the MP in most of the countries have traditionally been used to lower the inflation, to enhance long term development, for job creation, output growth, for balance-of-payments stability and to achieve sustainable growth.…”
Section: Introductionmentioning
confidence: 99%
“…The total influence of monetary policy (MP) on income inequality is theoretically unclear (Mäki-Fränti et al , 2022). However, some researchers indicate that expansionary and contractionary monetary policy reduces/increases income inequality (Andersen et al , 2021; Taghizadeh‐Hesary et al , 2020; Siami‐Namini et al , 2020; Hohberger et al , 2019). In their study, Adediran et al (2017) showed that the MP in most of the countries have traditionally been used to lower the inflation, to enhance long term development, for job creation, output growth, for balance-of-payments stability and to achieve sustainable growth.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, businesses depend on precise forecasts to inform critical decisions related to human resource planning, talent acquisition, and operational strategies. Understanding anticipated shifts in labor supply and demand enables companies to align their workforce strategies, optimize resource allocation, and enhance their competitive positioning [3]. Furthermore, individuals stand to gain significant benefits from unemployment rate forecasts as they make career decisions, evaluate job security, and plan for potential employment fluctuations.…”
Section: Introductionmentioning
confidence: 99%